Gender trouble : feminism and the subversion of identity - Butler, Judith (Routledge classics., 2006)
Since its initial publication in 1990, this book has become a key work of contemporary feminist theory, and an essential work for anyone interested in the study of gender, queer theory, or the politics of sexuality in culture. This is the text where the author began to advance the ideas that would go on to take life as "performativity theory," as well as some of the first articulations of the possibility for subversive gender practices. Overall, this book offers a powerful critique of heteronormativity and of the function of gender in the modern world.